Reduction of spinal cord injury with pentobarbital and hypothermia in a rabbit model - Tetik, Ö; Islamoglu, F; Göncü, T; Çekirdekçi, A; Büket, S (W B Saunders Co Ltd, 2002)
Objectives: to evaluate the effects of hypothermia and pentobarbital on spinal cord ischaemia induced in a rabbit model. Materials and Methods: thirty-two rabbits, allocated into four equal groups, had the infrarenal aorta clamped distal to the left renal artery and above the iliac bifurcation for 40 min. Groups 3 and 4 had infusion of 15 mg/kg of pentobarbital intravenously for 5 min, 15 min before the cross-clamping. Groups 2 and 4 had infusion of 20 ml of Ringer's lactate (LR) solution at 3degreesC for 3 min during aortic cross clamp into the isolated aortic segment. Group 1 was untreated and served as control. Postoperative functions of spinal cord were assessed. Results: paraplegia occurred in all rabbits in Group 1, in one in each of Groups 2 and 3, whereas no paraplegia was observed in Group 4. In addition 2 and 3 animals of Groups 2 and 3, respectively revealed varying degree of neurological disturbances, whereas all animals of Group 4 had normal function. This difference between Groups 2, 3, and 4 vs Group 1 was significant (p < 0.002). So was the difference between Groups 2 and 4 (p = 0.03), whereas the difference between Groups 3 and 4 was not significant. Conclusions: hypothermia and pentobarbital was more effective than hypothermia alone for prevention of spinal cord ischaemia in a rabbit model.
Keywords: spinal cord protection; paraplegia; ischaemic injury; pentobarbital